Design and Development of a Path-Tracking System Based on Radio Frequency Identification Sensor for Educational Toy Robot (EDOT) - Wicaksono, Martinus Bagus (International Journal of Applied Sciences and Smart Technologies, 2019)
This paper offers the design and development of a path-tracking system based on Radio Frequency Identification (RFID) sensors. This Path-tracking system will be used as a navigation system on EDOT. The EDOT requires a navigation system because it must be able to drive from the starting point to the predetermined end point automatically. This path-tracking system uses RFID sensors to detect RFID cards which have been arranged as a path. And then the EDOT will pass through the path consisting of some RFId cards. EDOT is a solution of a previous system, called Line-Follower, which uses infrared as a sensor to detect lines to guide a robot to go towards its destination point. The path-tracking system used by EDOT can work more efficiently in detecting the path to be traversed than other robots using the line follower system with infrared sensors or LDR (Light Dependent Resistor).Keywords: path-tracking, RFID, EDOT, robot